PENGARUH KETELADANAN GURU TERHADAP BUDI PEKERTI SISWA DI SMK 5 AGUSTUS PEKANBARU - Mardia Sri Malia; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the depletion of students’ morals and character in this increasingly advanced era which is heavily polluted by existing foreign cultures, this causes many students who do not respect their teachers. therefore, the author wants to research one of the schools in pekanbaru to see how the teacher’s role model influences the character of students at SMK 5 August Pekanbaru. This research is a quantitative research which is the sample of this study totaling 50 respondents. Data collection techniques using questionnaires, libraries, and documentation. The data analysis technique is by using simple linear regression with the formula Ý = a + bX. with the results of simple linear regression analysis, it is known that the regression aquation Ý = 46,180 + 0,399X, from the results of this equation, it can be concluded that the constant is 46,180 which means that the consistency value of student(Y) character variable is 46,180 while the regression coefficient of teacher(X) examplary is 0,399 which states that for every 1% addition of teacher(X) examplary level, student(Y) character will increase by 0,399. Based on the results of the research conducted, it can be concluded that there is an influence of teacher example on the character of students at SMK 5 August Pekanbaru.Key Words: Influence, Teacher’s Example, Student’s Character